A brief perspective on the fabrication of hierarchical nanostructure for solar water splitting photoelectrochemical cells - Kwon, Jinhyeong; Cho, Hyunmin; Lee, Habeom; Yeo, Junyeob; Hong, Sukjoon; Han, Seungyong; Ko, Seung Hwan (ECS Journal of Solid State Science and Technology, 2018)
Among various solar energy generation methods, a water splitting photoelectrochemical (PEC) cell have been anticipated as a one of the promising source to generate hydrogen by natural sunlight. Owing to unique electrical, electrochemical and optical properties, the nanostructured metal oxides were intensively investigated to adopt as a main material in the water splitting PEC cell. However, most of nanostructured metal oxides have an improper bandgap size/position for splitting water molecule, it needs to be engineered to shift a level of the energy bandgap. In this prospective review, we will briefly discuss solution-processed fabrication methods for water splitting applications.
Keywords: Energy generations; Fabrication method; Hierarchical Nanostructures; Nanostructured metals; Photoelectrochemicals; Solar water splitting; Solution-processed; Splitting waters